Plasmonic-resonance-based ternary composite complementary enhancement of the performance of dye-sensitized solar cells. (7th September 2016) - Bai, Lihua; Li, Meiya; Liu, Xiaolian; Luoshan, Mengdai; Zhang, Feng; Guo, Kaimo; Zhu, Yongdan; Sun, Beilei; Zhao, Xingzhong
Abstract: Graphene (G), TiO2 fusiform nanorods (TiO2 NRs) adsorbed with Au nanoparticles (AuNPs) are prepared and blended as multifunctional materials into TiO2 nanocrystalline film to form a novel ternary (G-TiO2 NRs-Au) composite photoanode in dye-sensitized solar cells (DSSCs). The effects of G-TiO2 NRs-Au on the properties of the photoanode and DSSC are investigated. Results show that, by blending G-TiO2 NRs-Au, the light absorption and scattering of the photoanode are obviously improved, and the charge transfer resistance R2 and electron recombination are decreased, resulting in a significant enhancement in the short-circuit current density ( J sc ) and the photoelectric conversion efficiency (PCE) of the DSSCs. The maximum J sc of 17.66 mA cm −2 and PCE of 8.56% are obtained in the optimal G-TiO2 NRs-Au-based DSSC, about 33.6% and 35.0% higher than that obtained in the conventional TiO2 -based DSSC. This significant improvement in the performance of the DSSC can be attributed to the ternary composite complementary effects of multi-functions from the surface plasmon resonance of AuNPs, light scattering of TiO2 NRs, and the improved dye loading and fast electron transmission channel from graphene. This study provides an effective way of ternary composite complementary enhancement of the J sc and PCE of the DSSCs.